Artificial intelligence in language instruction: impact on English learning achievement, L2 motivation, and self-regulated learning - Wei, Ling (Frontiers in Psychology, 2023)
This mixed methods study investigates the impact of AI-mediated language instruction on English learning achievement, L2 motivation, and self-regulated learning among EFL learners.Two intact classes (n = 60) from a university participated, with the experimental group exposed to AI-mediated instruction and the control group receiving traditional language instruction. Pretests and post-tests were conducted to assess English learning achievement in grammar, vocabulary, reading comprehension, and writing skills. Self-report questionnaires measured L2 motivation and self-regulated learning. Quantitative results revealed significantly higher English learning achievement in the experimental group, spanning multiple domains, and greater L2 motivation and self-regulated learning strategies. Additionally, qualitative analysis of semistructured interviews with 14 students from the experimental group highlighted the AI platform's transformative impact, fostering engaging and personalized learning experiences, enhancing motivation, and promoting self-regulated learning. These findings contribute to the growing research on AI-driven educational technologies, underscoring their potential to revolutionize language instruction. AI-mediated language instruction shows promise in improving language learning outcomes, motivating learners, and fostering autonomy. This study contributes to evidence-based language pedagogy, offering insights to educators and researchers seeking to integrate AI-powered platforms in language classrooms.